Keragaman Serangga Pengunjung pada Kelapa Sawit (Elaeis Guineensi Jacq.) di Kebun Pendidikan dan Penelitian (KP2) Stiper Edu Agro Tourism Ungaran - Handru, Alan; Putri, Diyona; Sidiq, M. Fajar (Program Studi Agroteknologi INSTIPER, 2023)
Oil palm (Elaeis guineensis Jacq.) productivity is highly dependent on insect pollination of flowers. Visiting insects are insects that come to a plant which can also act as pollinating insects. This study aims to investigate what insects visit oil palm trees. Research on the diversity of visitor insects on oil palms was conducted at Kebun Pendidikan dan Penelitian (KP2), Stiper Edu Agro Tourism (S.E.A.T), Ungaran in August and September, 2023. Sampling using hand collection, bait traps, bottle traps and sticky traps. Data were analyzed using Shannon Wiener Index and Sorensen Index. The study obtained a total of 1411 individuals consisting of 14 morphospecies, three orders, and three families of insects. The Diversity Index (H') in the interior of the plantation was H'=2.47 while at the edge of the plantation was H'=1.36. Similarity Index (S) was 96.29%. The dominant insect species is Elaeidobius kamerunicus (543 individuals) found on the anthesis male flowers of oil palms.